Ferramentas de diagnóstico da análise do comportamento nas organizações: uma análise do PDC, do PDC-HS e do PDC-Safety - Bergmann, Andreia (2020)
Performance management is the field of organizational behavior management (OBM) that studies individual or collective behavior in order to improve working conditions and employee productivity. The field has developed different evaluation tools to indicate possibilities for improvement. This research assessed three performance tools: (a) Performance Diagnostic Checklist (PDC); Performance Diagnostic Checklist – Human Services (PDC-HS); and (c) Performance Diagnostic Checklist – Safety (PDCSafety) through articles that have either applied the tools or discussed them theoretically. The assessment aimed to evaluate: (a) the methodological accuracy; (b) its prerequisites and when they are proposed; and (c) whether the suggested literature for interventions provides necessary and sufficient elements. From this analysis, the following factors were pointed out in order to receive better descriptions: choice of tool, interviews with supervisors and observations of the target tasks, calculations to identify problems, and choice of interventions based on the results